Hydrostatic Pressure Helps to Cultivate an Original Anaerobic Bacterium From the Atlantis Massif Subseafloor (IODP Expedition 357): Petrocella atlantisensis gen. nov. sp. nov. - Quéméneur, Marianne; Erauso, Gaël; Frouin, Eléonore; Zeghal, Emna; Vandecasteele, Céline; Ollivier, Bernard; Tamburini, Christian; Garel, Marc; Ménez, Bénédicte; Postec, Anne (Frontiers in Microbiology, 2019)
Rock-hosted subseafloor habitats are very challenging for life, and current knowledge about microorganisms inhabiting such lithic environments is still limited. This study explored the cultivable microbial diversity in anaerobic enrichment cultures from cores recovered during the International Ocean Discovery Program (IODP) Expedition 357 from the Atlantis Massif (Mid-Atlantic Ridge, 30°N). 16S rRNA gene survey of enrichment cultures grown at 10–25°C and pH 8.5 showed that Firmicutes and Proteobacteria were generally dominant. However, cultivable microbial diversity significantly differed depending on incubation at atmospheric pressure (0.1 MPa), or hydrostatic pressures mimicking the in situ pressure conditions (8.2 or 14.0 MPa). An original, strictly anaerobic bacterium designated 70B-AT was isolated from core M0070C-3R1 (1150 mbsl; 3.5 mbsf) only from cultures performed at 14.0 MPa. This strain named ‘Petrocella atlantisensis’ is a novel species of a new genus within the newly described family ‘Vallitaleaceae’ (order Clostridiales, phylum Firmicutes). It is a mesophilic, moderately halotolerant and piezophilic chemoorganotroph, able to grow by fermentation of carbohydrates and proteinous compounds. Its 3.5 Mb genome contains numerous genes for ABC transporters of sugars and amino acids, and pathways for fermentation of mono- and di-saccharides and amino acids were identified. Genes encoding multimeric [FeFe] hydrogenases and a Rnf complex form the basis to explain the hydrogen and energy production in strain 70B-AT. This study outlines the importance of using hydrostatic pressure in culture experiments for isolation and characterization of autochthonous piezophilic microorganisms from deep subseafloor rocks.